Win with English : - McLean, Alan C (Oxford University Press, 2000)
The book is a comprehensive three-level course, designed to improve student’s competence in English and broaden their horizons. Each level consists of a student’s book, a workbook, a teacher’s book and a cassette. This book approaches the four skills of listening, speaking, reading anf writing in an integrated and balanced manner